Fanfiction: reading and writing in the digital age - Paula, Luciane de [UNESP]; Zandonadi, Raquel Santos [UNESP] (Univ Estadual Oeste Parana-unioeste, 2020)
Based on the premise that society becomes more digital and that people increasingly read and write in cyberspace, this proposal aims to reflect on the fanfiction?s discursive genre (fan writing) and relate it to teaching practices, considering that the schools should not be unaware of the diversity of languages and cultures in the technological world, and that it should address discursive genres as social practices in order to form multi -literate citizens. This is a reflection on a qualitative research, based on both the Bakhtinian studies to think about genders; as well as on multiliteracies studies and on Jenkins' notion of participatory culture. The results demonstrate the urgency of working with multimodal genres in the classroom and the need to adapt the school to the context.
Keywords: contemporary Discursive genres; Participatory culture; Literacies